Bewilderment: a novel (Thorndike Press large print core, ,, 2022)
"A heartrending new novel from the Pulitzer Prize-winning and #1 New York Times best-selling author of The Overstory. "Richard Powers, whose novels combine the wonders of science with the marvels of art, astonishes us in different ways with each new book." -Heller McAlpin, NPR Books. The astrobiologist Theo Byrne searches for life throughout the cosmos while single-handedly raising his unusual nine-year-old, Robin, following the death of his wife. Robin is a warm, kind boy who spends hours painting elaborate pictures of endangered animals. He's also about to be expelled from third grade for smashing his friend in the face. As his son grows more troubled, Theo hopes to keep him off psychoactive drugs. He learns of an experimental neurofeedback treatment to bolster Robin's emotional control, one that involves training the boy on the recorded patterns of his mother's brain. . . . With its soaring descriptions of the natural world, its tantalizing vision of life beyond, and its account of a father and son's ferocious love, Bewilderment marks Richard Powers's most intimate and moving novel. At its heart lies the question: How can we tell our children the truth about this beautiful, imperiled planet?" --

Lost in the forest (Knopf, Random House Large Print, Random House Publishing Group, Books on Tape, Random House Audio, 2006)
A novel set in the vineyards of Northern California that tells the story of a young girl who, in the wake of a tragic accident, seeks solace in a damaging love affair with a much older man. Eva, a divorced and happily remarried mother of three, runs a small bookstore in a town north of San Francisco. When her second husband, John, is killed in a car accident, her family's fragile peace is once again overtaken by loss. Emily, the eldest, must grapple with newfound independence and responsibility. Theo, the youngest, can only begin to fathom his father's death. But for Daisy, the middle child, John's absence opens up a world of bewilderment, exposing her at the onset of adolescence to the chaos and instability that hover just beyond the safety of parental love. In her sorrow, Daisy embarks on a harrowing sexual odyssey, a journey that will cast her even farther out onto the harsh promontory of adulthood and lost hope.

A grief observed (Warbler Classics, Bantam Books, Phoenix Press, Playaway Digital Audio, HarperCollins, Harper & Row, Blackstone Audiobooks, HarperSanFrancisco, HarperAudio, Blackstone Publishing, HarperCollins Publishers, 2009)
The author recounts his grief over the death of his wife, and explains how he reexamined his religious beliefs.

The echo maker (Farrar, Straus and Giroux, BBC Audiobooks America, Blackstone Publishing, Thorndike Press, 2007)
Winner of the National Book Award From the Pulitzer Prize–winning author of The Overstory and the Oprah's Book Club selection Bewilderment comes Richard Powers's The Echo Maker, a powerful novel about family and loss. "Wise and elegant . . . The mysteries unfold so organically and stealthily that you are unaware of his machinations until they come to stunning fruition . . . Powers accomplishes something magnificent." —Colson Whitehead, The New York Times Book Review On a winter night on a remote Nebraska road, twenty-seven-year-old Mark Schluter has a near-fatal car accident. His older sister, Karin, returns reluctantly to their hometown to nurse Mark back from a traumatic head injury. But when Mark emerges from a coma, he believes that this woman—who looks, acts, and sounds just like his sister—is really an imposter. When Karin contacts the famous cognitive neurologist Gerald Weber for help, he diagnoses Mark as having Capgras syndrome. The mysterious nature of the disease, combined with the strange circumstances surrounding Mark's accident, threatens to change all of their lives beyond recognition. In The Echo Maker, Richard Powers proves himself to be one of our boldest and most entertaining novelists.

Small days and nights (W. W. Norton & Company, HighBridge, 2020)
"A captivating and original story of two sisters caught in a moment of transformation, set against the vivid backdrop of modern India. Escaping her failing marriage, Grace Marisola has returned to Pondicherry from the United States to cremate her mother. Once there, she receives an inheritance she could not have expected-a property on the beaches of Madras-and discovers a sister she never knew she had: Lucia, who was born with Down Syndrome and has spent her life in a residential facility. Grace sets up a new and precarious life with Lucia; the housekeeper, Mallika; drily witty Auntie Kavitha; and an ever- multiplying litter of puppies. But Grace's attempts to leave her old self behind and create a new family prove first a struggle, then a strain, as she discovers the chaos, tenderness, fury and bewilderment of life with Lucia. [...] Small Days and Nights is a story of the ties that bind, the secrets we bury, and the sacrifices we make to forge lives that have meaning"--

Farewell to Manzanar (Clarion Books, HarperCollins, Findaway World, LLC, 2019)
The powerful true story of life in a Japanese American internment camp. During World War II the community called Manzanar was hastily created in the high mountain desert country of California, east of the Sierras. Its purpose was to house thousands of Japanese American internees. One of the first families to arrive was the Wakatsukis, who were ordered to leave their fishing business in Long Beach and take with them only the belongings they could carry. For Jeanne Wakatsuki, a seven-year-old child, Manzanar became a way of life in which she struggled and adapted, observed and grew. For her father it was essentially the end of his life. In Farewell to Manzanar, Jeanne Wakatsuki Houston recalls life at Manzanar through the eyes of the child she was. She tells of her fear, confusion, and bewilderment as well as the dignity and great resourcefulness of people in oppressive and demeaning circumstances. Jeanne delivers a powerful first-person account that reveals her search for the meaning of Manzanar. Farewell to Manzanar has become a staple of curriculum in schools and on campuses across the country. Named one of the twentieth century's 100 best nonfiction books from west of the Rockies by the San Francisco Chronicle.

The frozen crown: a novel (Warrior witch duology, 1,, 2021)
"Askia became heir to the Frozen Crown of Seravesh because of her devotion to her people. But her realm is facing a threat she cannot defeat by sheer will alone. The mad emperor of the Roven Empire has unleashed a horde of invading soldiers to enslave her lands. For months, her warriors have waged a valiant, stealth battle, yet they cannot stop the enemy's advancement. Running out of time, she sets sail for sun-drenched Vishir, the neighboring land to the south, to seek help from its ruler, Emperor Armaan. A young woman raised in army camps, Askia is ill-equipped to navigate Vishir's labyrinthine political games. Her every move sinks her deeper into court intrigues which bewilder and repel her, leaving her vulnerable not only to enemies gathering at Vishir's gates, but to those behind the palace walls. And in this glittering court, where secrets are worth more than gold, Askia fears that one false step will expose her true nature. For Askia is a witch gifted with magical abilities--knowledge that could destroy not only her life but her people. As her adversaries draw closer, Askia is forced to make an impossible choice--and no matter what she decides, it may not be enough to prevent Seravesh's fall. "--Provided by publisher.

The adventures of Sally (Jeeves, ,, 2018)
Pretty, impecunious Sally Nicholas never dreamed a fortune could prove a disadvantage, until she becomes and heiress and watches in bewilderment as her orderly existence goes haywire. Coping first with her brother's wild theatrical ambitions, then with the defection of her fiance and his immediate replacement by a much more appropriate but strangely attractive suitor, Sally finds that life in New York is becoming altogether too complicated. A trip to England only makes the whole situation worse. But just as Sally is concluding that she has disastrously misplaced her bets, it looks as if a piece of speculation on an outsider might just give her a happy ending.

The highest tide: a novel (Audio Renaissance, Bloomsbury USA, Macmillan Audio, Bloomsbury Publishing, 2005)
A stunning coming-of-age novel about one boy's mystical bond to the sea. "[A] graceful and inventive first novel." -The New York Times Book Review "The fertile strangeness of marine tidal life becomes a subtly executed metaphor for the bewilderments of adolescence in this tender and authentic coming-of-age novel." -Publishers Weekly "As crisp and clean as a cool dip into the water, and just about as refreshing." -Entertainment Weekly "Move over, Holden Caulfield; here's Miles. . . . An uncommon and uncommonly good coming-of-age novel." -Chicago Tribune One moonlit night, thirteen-year-old Miles O'Malley sneaks out of his house and goes exploring on the tidal flats of Puget Sound. When he discovers a rare giant squid, he instantly becomes a local phenomenon. But Miles is really just a kid on the verge of growing up, infatuated with the girl next door, worried that his parents will divorce and fearful that everything, even the bay he loves, is shifting away from him.

The Dog of Tithwal: Stories (Tantor Media, Inc., Steerforth Press, 2022)
“[Manto’s] empathy and narrative economy invite comparisons with Chekhov. These readable, idiomatic translations have all the agile swiftness and understated poignancy that parallel suggests." —-Boyd Tonkin, Wall Street Journal Stories from "the undisputed master of the modern Indian short story" encircling the marginalized, forgotten lives of Bombay, set against the backdrop of the India-Pakistan Partition (Salman Rushdie) By far the most comprehensive collection of stories by this 20th Century master available in English.   A master of the short story, Saadat Hasan Manto opens a window onto Bombay’s demimonde—its prostitutes, rickshaw drivers, artists, and strays as well probing the pain and bewilderment of the Hindus, Muslims, and Sikhs ripped apart by the India-Pakistan Partition.   Manto is best known for his dry-eyed examination of the violence, horrors, and reverberations from the Partition. From a stray dog caught in the crossfire at the fresh border of India and Pakistan, to friendly neighbors turned enemy soldiers pausing for tea together in a momentary cease fire—Manto shines incandescent light into hidden corners with an unflinching gaze, and a fierce humanism.   With a foreword by Pulitzer Prize–winning poet Vijay Seshadri, these stories are essential reading for our current moment where divisiveness is erupting into violence in so many parts of the world.

Age of anger: a history of the present (Tantor Media, Inc., Farrar, Straus and Giroux, 2017)
"One of our most important public intellectuals reveals the hidden history of our current global crisis. How can we explain the origins of the great wave of paranoid hatreds that seem inescapable in our close-knit world--from American 'shooters' and ISIS to Trump, from a rise in vengeful nationalism across the world to racism and misogyny on social media? In Age of Anger, Pankaj Mishra answers our bewilderment by casting his gaze back to the eighteenth century, before leading us to the present. He shows that as the world became modern those who were unable to fulfill its promises--freedom, stability and prosperity--were increasingly susceptible to demagogues. The many who came late to this new world or were left, or pushed, behind, reacted in horrifyingly similar ways: intense hatred of invented enemies, attempts to re-create an imaginary golden age, and self-empowerment through spectacular violence. It was from among the ranks of the disaffected that the militants of the 19th century arose--angry young men who became cultural nationalists in Germany, messianic revolutionaries in Russia, bellicose chauvinists in Italy, and anarchist terrorists internationally. Today, just as then, the wider embrace of mass politics, technology, and the pursuit of wealth and individualism has cast many more billions adrift in a literally demoralized world, uprooted from tradition but still far from modernity--with the same terrible results. Making startling connections and comparisons, Age of Anger is a book of immense urgency and profound argument. It is a history of our present predicament unlike any other"--
Prologue: Forgotten Conjunctures , Clearing a Space : History's Winners and their Illusions , Loving Oneself Through Others : Progress and its Contradictions , Losing My Religion : Islam, Secularism and Revolution , Regaining My Religion : I. Nationalism Unbound; I I. Messianic Visions , Finding True Freedom and Equality : The Heritage of Nihilism , Epilogue: Finding Reality.

The maze at Windermere: a novel (Thorndike Press large print historical fiction, ,, 2018)
"A richly layered novel of love, ambition, and duplicity, set against the storied seascape of Newport, Rhode Island. A reckless wager between a tennis pro with a fading career and a drunken party guest--the stakes are an antique motorcycle and an heiress's diamond necklace--launches a narrative odyssey that braids together three centuries of aspiration and adversity. A witty and urbane bachelor of the Gilded Age embarks on a high-risk scheme to marry into a fortune; a young writer soon to make his mark turns himself to his craft with harrowing social consequences; an aristocratic British officer during the American Revolution carries on a courtship that leads to murder; and, in Newport's earliest days, a tragically orphaned Quaker girl imagines a way forward for herself and the slave girl she has inherited. In The Maze at Windermere Gregory Blake Smith weaves these intersecting worlds into a brilliant tapestry, charting a voyage across the ages into the maze of the human heart"--

Nemesis (Brilliance Audio on compact disc, ,, 2010)
Roth's "Nemesis" is the story of a wartime polio epidemic in the summer of 1944 and the effect it has on a closely knit, family-oriented Newark community and its children.

We are okay (Printz Award Winner, ,, 2017)
After leaving her life behind to go to college in New York, Marin must face the truth about the tragedy that happened in the final weeks of summer when her friend Mabel comes to visit.

Archer's quest (Clarion Books, HarperCollins, Books on Tape, 2007)
Twelve-year-old Kevin Kim helps Chu-mong, a legendary king of ancient Korea, return to his own time.

Leaving the witness: exiting a religion and finding a life (Books on Tape, Viking, 2019)
A first book by the creator of the "Dear Amber" podcast describes her strict upbringing as a third-generation Jehovah's Witness and her efforts to find her true place in the world apart from the edicts of her family and faith. A third-generation Jehovah's Witness, Scorah had devoted her life to sounding God's warning of impending Armageddon. She took the message to China, where immersion in a foreign language and culture turned her world upside down, and eventually led her to lose all that she had been sure was true. Beginning to understand that there were other ways of seeing the world, her loss of faith culminated in her own personal apocalypse. Shunned by family and friends as an apostate, Scorah was thrown into a world she had only known from the periphery. Here she examines what it's like to start one's life over again with an entirely new identity, trying to find meaning in the absence of religion.-- adapted from jacket

The governess of Penwythe Hall (Cornwall novels, 1,, 2019)
"In the first of a new series from beloved Regency romance author, Sarah Ladd, Delia, a governess to five recently orphaned children, would risk anything to protect them . . . even her heart"--

The rough patch: marriage and the art of living together (Simon & Schuster Audio, Scribner, an imprint of Simon & Schuster, Inc, 2018)
"People today are trying to make their marriages work over longer lives than ever before-- but staying married isn't always easy. De Marneffe addresses key problems that challenge marriages, and explains the psychological, emotional, and relational capacities we must cultivate to overcome them as individuals and as couples." --
The rough patch: an introduction , A brief history of the midlife crisis , Feeling close, in love and sex , Marriage as a story , Affairs, flirting, and fantasy: they're never about nothing , Alcohol and other attempted escapes , Money: the knife in the drawer , Lovesickness and longing: putting them to use , Body, health, and age: the stakes only get higher , The empty nest: children, parents, and the turning of the generations , Staying or leaving , Love is a conversation.

How to Manage Your Home without Losing Your Mind: Dealing with Your House's Dirty Little Secrets (Thomas Nelson, 2016)
Bring your home out of the mess it's in—and learn how to keep it under control! Housekeeping expert Dana K. White shares reality-based cleaning and organizing techniques that will help you learn what really works. Do you experience heart palpitations at the sound of an unexpected doorbell? Do you stare in bewilderment at your messy home, wondering how in the world it got this way again? You're not alone. But there is hope for you and your home. Managing your home isn't an all-or-nothing approach, and Dana has broken down the most critical things that you'll need to do to keep up with the housework. With understanding, honesty, and her trademark humor, Dana shares her field-tested strategies including: Exactly where to start to tame the chaos Which habits deserve your focus and will make the most impact How to gain traction in your quest for a manageable home Practical tips you can implement and immediately to declutter huge amount of stuff with minimal emotional drama Cleaning your house is not a one-time project—it's a series of ongoing and daily decisions. Start learning Dana's reality-based cleaning and organizing techniques—and see how they really work! Praise from Readers: "This book lays out the hard truths of a clean house but in a way that doesn't make me feel silly for not having embraced them before." "Dana leads you step-by-step with the heart of a woman who has been there and struggled with the same issues you are currently struggling with. Really, this is a must read for anyone who wants to learn the secrets that all those organized types seem to know." "I felt like a failure already. Did I really need to read yet another book full of tips and tricks that would leave me feeling worse? From the first page, I was put at ease." Get ready to say goodbye to the stacks of dirty dishes crowding your kitchen counters, conquer the never-ending piles of laundry, and stop tripping over clutter on your living room floor as Dana helps you discover what works for you, for your unique personality, and in your unique home.

Nineteen eighty-four, a novel (Classic ed, ,, 2021)
"A chilling portrait of a totalitarian society under the ever-watchful gaze of Big Brother, where love, privacy, and individuality are banned. The year 1984 has come and gone, but George Orwell's nightmare vision from 1949 of the world we are becoming is timelier that ever. 1984 is the great modern classic of a 'negative utopia' - a startlingly original and haunting novel that creates an imaginary world that is completely convincing" --
Introduction / Julian Symons --, Select bibliography , Chronology , Textual note , [The work]: Nineteen eighty-four , Appendix:, The principles of newspeak.